Organic Diseases, Orofacial Motricity and Speech Disorders in Childrens with Feeding Diffi culties - Ramos, Claudia de Cássia (2022)
Introduction: Organic diseases (OD) and changes in orofacial motricity can be causes associated with feeding difficulties (FD) in childhood.Objective: To describe the prevalence of orofacial motricity, speech and language disorders in children with FD according to the presence or absence of associated OD.Material and Methods: Retrospective observational study based on the use of information collected from medical records authorized for scientific use. The study population consisted of children with FD complaints treated in outpatient service. A structured questionnaire, physical and food assessment were used to collect information.Results: Of the 189 children studied, 69.8% had no associated OD. The group with OD presented a higher prevalence of alterations for all orofacial motricity variables, however, there were statistically significant differences only for speech disorders (p = 0.046), language disorders (p = 0.020) and changes in tone (p = 0.035). Children with language disorders had a higher frequency of allergy (p = 0.002).Conclusion: The group with OD showed a higher prevalence of alterations for all orofacial motricity and speech variables, with statistically significant differences for speech disorders, language disorders and tone changes.